2016
DOI: 10.2147/ndt.s120786
|View full text |Cite
|
Sign up to set email alerts
|

Association between serotonin transporter gene polymorphisms and heroin dependence: a meta-analytic study

Abstract: BackgroundStudies have examined the association between heroin dependence and serotonin transporter gene polymorphisms but yielded inconsistent results. The purpose of current study is to determine the overall effect of these polymorphisms on the risk for heroin dependence through a meta-analytic method.MethodsA meta-analysis was conducted to examine the association of heroin dependence with two common polymorphisms of serotonin transporter gene, in the promoter (5-hydroxytryptamine transporter-linked promotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Although there are likely multiple contributing factors in developing substance dependences, including multiple genes with subtle effects, this study was focused on the tandem repeats in the functional polymorphism in the SERT promoter (5-HTTLPR) in a cohort of subjects of European ancestry from the Netherlands, including subjects with current opioid dependence, lifetime opioid use without opioid dependence, and healthy controls. In contrast to some previous findings showing a significant association of heroin dependence with the S allele of 5-HTTLPR in Caucasians, 20 , 22 , 23 we did not find a significant association of short (S) or long (L) forms of the repeats with the categorical opioid dependence diagnosis. Reasons for this discrepancy include methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although there are likely multiple contributing factors in developing substance dependences, including multiple genes with subtle effects, this study was focused on the tandem repeats in the functional polymorphism in the SERT promoter (5-HTTLPR) in a cohort of subjects of European ancestry from the Netherlands, including subjects with current opioid dependence, lifetime opioid use without opioid dependence, and healthy controls. In contrast to some previous findings showing a significant association of heroin dependence with the S allele of 5-HTTLPR in Caucasians, 20 , 22 , 23 we did not find a significant association of short (S) or long (L) forms of the repeats with the categorical opioid dependence diagnosis. Reasons for this discrepancy include methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
“…There were no differences in the reduction in cocaine use across the LL, LS and SS genotypes, in African-American patients with cocaine dependence. 20 Studies of cocaine dependence diagnosis as a categorical endpoint did not detect a robust association with 5-HTTLPR genotype, either in Spanish 24 or African-American cohorts. 25 In another study, carriers of the S allele reported greater “desire” and other subjective effects after challenge with intravenous cocaine injection.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…According to a meta-analysis by Lin and Wu [35], the 'S' allele has been found to be more common in the opioid-dependent population. The 'S' allele has reduced transcriptional activity and is associated with impulsive behavior, suicidal attempts, and violent behavior.…”
Section: Discussionmentioning
confidence: 99%